Sintesis Etil Stearat dari Reaksi Esterifikasi Asam Stearat dan Etanol Menggunakan Katalis Asam Sulfat - Nitbani, Febri O.; Sabu, Marselina; Wogo, Hermania Em; Cunha, Theo Da (Universitas Nusa Cendana, 2021)
The study about Synthesis of Ethyl Stearate through Esterification Reaction of Stearic Acid and Ethanol Using Sulfuric Acid Catalysis had carried out. The purpose of this study is to know how to synthesize Ethyl Stearate from esterification reaction of stearic acid and ethanol using sulfuric acid catalyst. Characterization of Ethyl Stearate compound was done using FT-IR and GC-MS. The study result exhibits that the yield of Ethyl Stearate product obtained is 98.85 %. Through characterization using FT-IR and GC-MS can be concluded that Ethyl Stearate compound is successfully synthesized and its purity reaches 98.87%.